The problems of the providing the law in the theory of public administration - Бєлкін, Леонід Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The certain theoretical and applied aspects of the law issues solutions in the theory of public administration are explored. It is shown that the consideration of the public administration in the context of European administrative law needs appropriate approaches to the providing of law, which may differ from those traditionally adopted in the law implementation system in the activities of the executive branch. The above is because the European understanding of «public administration» means the service for citizens and society. Ukrainian public servants mostly do not have this understanding. Particular attention should be paid to the Association Agreement Ukraine – EU goals of political dialogue between the parties by «strengthen respect for democratic principles, the rule of law and good governance, human rights and fundamental freedoms». The set of reasoning leads to the conclusion that the public administration in the European sense of the term is not just a set of government agencies in the conventional sense of the word, they perform public administration on the principles of «good governance». The aim of «good governance» is not to achieve results at all costs, but to build a transparent process of policy implementation based on broad participation of citizens and in their interests. One of the main principles of «good governance» is the implementation of «public administration» based on the rule of law. The Constitution of Ukraine expressly provided several features of the implementation of the rule of law in administrative relationship. It is established that a rule of law means a justice and equality before the law. Under these conditions, the question concerning the obligation of the authorities to refrain from abusing the discretion powers and act the same way in the same cases, remains actual. The European administrative law requires that the subject of authority must follow the principle of unity of law and avoid adopting different solutions in the same situations. There is also still a question of effective judicial monitoring of government discretion powers. Implementing the theory of public administration in administrative law Ukraine meets European course of Ukraine.